Evaluation of Malaria Transmission and Vector Control Strategies in the Dry Season in the Cotonou V Health Zone, Benin, West Africa - Tokponnon, Tatchémè Filémon (My University, 2023)
The anarchic urbanization of certain African cities favors the multiplication of the malaria parasite. Thus, the urgent mobilization of African cities is essential to combat this health risk. It is, therefore, with the objective of contributing to the investigation of problem areas that the present study evaluates malaria transmission and vector control strategies in the Cotonou V health zone in particular. This is a cross-sectional study taking into account four neighborhoods, including Wologuèdè, Sainte Rita, Gbèdjromèdé and the area around Etoile Rouge. Two nocturnal captures on voluntary humans and the method of spray were carried out in the dry season from December 2021 to February 2022. On the captured Anopheles, the ELISA Circum-Sporozoite Protein test was performed to determine the infectivity and calculate some transmission parameters. Finally, we conducted a survey using the second stage sampling method with one step to ask selected households about their knowledge of vector control methods, their use and the physical integrity of LLINs. We collected 2386 culicidae of which the majority was Culex quinquefasciatus. After the ELISA test, the 29 Anopheles tested, showed no infectivity, i.e. an EIR of 0 pi/h/n. In addition, 99% of the populations in the Cotonou V area use LLINs to protect themselves. However, coils, door and window screens, aerosol sprays, skin and household repellents, and periodic indoor spraying were used. Finally, the majority of nets observed had T1 tears, but there were also T2, T3 and T4 nets (P-value = 0.0). This study confirms that malaria transmission during the dry season in the Cotonou V health zone is almost negligible but not non-existent. Also, populations are exposed to the nuisance of Culex quinquefasciatus mosquitoes continuously throughout the year.
Keywords: Anopheles; Transmission; Urban Malaria; Cotonou V Health Zone; Vector Control